The free-living phase of Boophilus microplus in the Santa Catarina plateau area - Souza, Antonio Pereira de; Gonzales, João Carlos; Ramos, Cesar Itaqui; Paloschi, Claudio Granzotto; Moraes, Aury Nunes de (Pesquisa Agropecuaria Brasileira, 2014)
From March 1979 to February 1982, two groups of 5 g of Boophilus microplus (Can 1887) engorged female ticks monthly Boophilus microplus exposed to the environment in Petri dishes protected from direct sun light. Egg production, pre-oviposition, oviposition, pre-hatching and neolarval period, and the longevity of the infesting larvae, were noted twice a week. Mean monthly temperature and relative humidity were also registered. The minimum periods of pre-oviposition, oviposition, pre-hatching, neolarval and longevity, of the infesting larvae were 4, 17, 15, 3 and 30 days, respectively, while the maximum periods were 87, 67, 185, 14 and 286 days, respectively. The average egg mass varied from 2.352 g to 0.056 g. The eggs derived from engorged female exposed to the environment from April to August were infertile. It was also observed that during the months of January and February a certain concentration of hatching of larvae took place from groups of engorged females with fertile egg masses.
Keywords: Boophilus microplus; egg production; pre-oviposition; oviposition; pre-hatching; neolarval period; longevity larval